2019
DOI: 10.1073/pnas.1820161116
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt is inhibited by targeting one-carbon metabolism through methotrexate or methionine deprivation

Abstract: The nutrient-sensing metabolite S-adenosylmethionine (SAM) controls one-carbon metabolism by donating methyl groups to biochemical building blocks, DNA, RNA, and protein. Our recent work uncovered a requirement for cytoplasmic arginine methylation during Wnt signaling through the activity of protein arginine methyltransferase 1 (PRMT1), which transfers one-carbon groups from SAM to many protein substrates. Here, we report that treatments that decrease levels of the universal methyl donor SAM were potent inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 87 publications
(154 reference statements)
2
48
0
Order By: Relevance
“…Several signaling molecules have been found to participate in the formation and development of follicles, and these include Wnt/β-catenin, Sonic Hedgehog, bone morphogenetic proteins, and Notch ( Harris et al., 2010 ; Ouji et al., 2013 ; Ouspenskaia et al., 2016 ; Cheng et al., 2018 ). Albrecht et al. (2019) proved that Met deficiency causes a decrease in Wnt/β-catenin activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several signaling molecules have been found to participate in the formation and development of follicles, and these include Wnt/β-catenin, Sonic Hedgehog, bone morphogenetic proteins, and Notch ( Harris et al., 2010 ; Ouji et al., 2013 ; Ouspenskaia et al., 2016 ; Cheng et al., 2018 ). Albrecht et al. (2019) proved that Met deficiency causes a decrease in Wnt/β-catenin activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on the effects of L- or DL-Met on the development of feather follicles are limited to descriptions of characteristics and molecular mechanisms have rarely been reported. Albrecht et al. (2019) revealed that L-Met deletion disrupts Wnt/β-catenin signaling in HeLa cells, and this disruption can be rescued by S-adenosylmethionine ( SAM , a direct metabolite of Met) supplementation during Met depletion.…”
Section: Introductionmentioning
confidence: 99%
“…2). Conversely, methotrexate could be used to treat Wnt-driven malignancies by suppressing SAM levels and blocking arginine methylation (Albrecht et al, 2019). Similarly, inhibiting the synthesis or utilization of SAM could curtail acquired resistance by preventing transdifferentiation mechanisms and by effectively removing TICs that might cause cancer recurrence (Reina-Campos et al, 2019;Visvader and Lindeman, 2008;Wang et al, 2019).…”
Section: Pending Questions and Potential New Therapeutic Opportunitiesmentioning
confidence: 99%
“…It is known that Notum is regulated by β-catenin and change in spatial expression of Notum suggests potential changes in β-catenin activity [35]. Given the recently shown importance of methylation and one-carbon metabolism in canonical Wnt signaling by De Robertis group, we speculate that disruption of the methionine cycle may lead to failure in planarian body plan maintenance via changes in Wnt signaling [36], [37]. Although we did not find β-catenin target genes among differentially expressed genes in AdOx-adapted worms, it does not exclude possible changes in post-translational regulation.…”
Section: Discussionmentioning
confidence: 99%